Métodos de aplicação de inseticida no manejo populacional da broca-do-café, Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Scolytidae) - Parenti, Matheus Vilhena (2020)
The coffee borer is considered one of the major coffee pests in Brazil. Damage caused by the insect affects the quantity and quality of grain production. Due to inefficient harvesting, fruits left unharvested and on the ground contribute to the maintenance of the borer life-cycle, increasing its presence at each harvest. Chemical control, essential for efficient management, needs to ensure the insect is contaminated by the insecticide in a safe way for the environment. Nowadays, more modern and safer insecticides are being developed, but at higher costs, requiring more assertive spraying, crucial for production sustainability especially regarding the penetration of the syrup canopy and the reduction of drift losses. This study aimed at analyzing the agronomic efficacy and the deposition of sprayed syrup on coffee fruits and leaves and to estimate the soil loss due to the use of different rates and spray tips. The experiment was carried out in an additional 2 x 2 + 1 factorial scheme and six replications, with the spray tip factors (JA1 empty conical jet and TVI empty conical jet) and spray application rates (200 and 400 L ha-1), and an additional SPE2 tip with electrostatic system (200L ha-1). The applications were performed using a hydropneumatic spray and the Bright Blue marker, which was quantified by spectrophotometry. Fruits and leaves were collected from the thirds of the plants and also Petri dishes positioned near the soil surface were used for deposit evaluation. The efficacy evaluation counted the incidence of damaged fruits twenty-forty days after application. There was a significant increase in the deposition of syrup in the fruits of the middle third and in the soil plate by the air-induced nozzle, which also demonstrated superiority in control.